Preparation method of electrically-driven piezoelectric catalytic electrode and method for deep dehydration of organic solid waste by using electrically-driven piezoelectric catalytic electrode
By combining MoS2-based piezoelectric material with titanium-based ruthenium iridium electrode, the interface potential of organic solid waste is regulated and the extracellular polymer structure is destroyed, and the problem of deep dehydration of organic solid waste in the prior art is solved, and efficient deep dehydration effect is achieved. Reduces costs and energy consumption and avoids secondary pollution.
Patent Information
- Application Number
- CN202411307193.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The existing piezoelectric dehydration technology has poor effect on removing bound water and interstitial water with strong binding capacity. It often requires chemical agent assistance or strict operating conditions, making it difficult to achieve deep dehydration of organic solid waste.
MoS2-based piezoelectric material is used to combine with titanium-based ruthenium iridium electrodes, and the Zeta potential of the interface between organic solid waste and solution is regulated through an electrocatalytic system, destroy the extracellular polymer structure, release bound water and interstitial water, and achieve deep dehydration of organic solid waste. .
Without chemical agents, the moisture content of organic solid waste is significantly reduced, from 40% to 60% to 30.7% to 46.3%, the deep dehydration efficiency is as high as 9.3% to 13.7%, and the cost is low and energy consumption is low. There is no risk of secondary pollution.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of deep dehydration and reduction of organic solid waste, and more specifically, relates to a method for deep dehydration of organic solid waste and a piezoelectric catalytic electrode and a method for preparing the electrode. Background Art
[0002] Reducing the moisture content of organic solid waste, especially improving the deep dehydration capacity of organic solid waste, is a key issue that needs to be broken through in my country's solid waste reduction. Traditional dehydration technology has a strong ability to remove free water with weak binding capacity, but the removal effect on bound water and interstitial water with strong binding capacity is not ideal. Therefore, the development of new technologies for deep dehydration of organic solid waste is of extremely important practical significance.
[0003] Piezoelectric dehydration is an emerging dehydration technology that uses the piezoelectric effect to generate a polarized electric field, destroy extracellular polymers, release bound water, and achieve deep dehydration of river and lake sediments. Currently, reports related to piezoelectric dehydration mainly focus on barium titanate, but the presence of composite piezoelectric catalytic materials requires the assistance of chemical agents (co-catalysts, coagulants and flocculants, etc.) (201911289167.3, 202010972300.1, Water Res. , 209 (2022) 117922) or harsh operating conditions (202311791903.1, Nat. Commun. 15 (2024) 4845) and other issues.
[0004] The piezoelectric effect is a physical phenomenon that refers to the deformation of piezoelectric materials under external stress, which causes the material to spontaneously polarize, forming a built-in electric field and induced charges on the surface of the material. When the piezoelectric material is deformed and generates a built-in electric field, its band structure changes, making the material catalytically active. MoS2 has a two-dimensional S-Mo-S layered structure, and the layers are attracted to each other by van der Waals forces. At present, there are no reports on the deep dehydration of organic solid waste using the piezoelectric properties of MoS2. Summary of the invention
[0005] The purpose of the present invention is to provide a method for deep dehydration and reduction of organic solid waste, and an electrically driven piezoelectric catalytic electrode material and a preparation method thereof. The method utilizes the strong piezoelectric properties of MoS2 to regulate the Zeta potential of the interface between organic solid waste and solution, destroy the extracellular polymer structure on the surface of organic solid waste, release bound water and interstitial water, and achieve the purpose of deep dehydration of organic solid waste without adding chemical agents, thereby solving the technical problem of deep dehydration of organic solid waste.
[0006] To achieve the above object, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing an electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste, comprising the following steps: S1, mixing a molybdenum source, a sulfur source and a solvent for a solvothermal reaction to obtain a MoS2-based piezoelectric material; The MoS2-based piezoelectric material includes any one of a MoS2 piezoelectric material, a sulfur-defective MoS2 piezoelectric material, and a molybdenum-defective MoS2 piezoelectric material; S2. Mix the MoS2-based piezoelectric material, titanium-based ruthenium-iridium electrode and water to carry out a hydrothermal reaction to obtain the electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste.
[0007] In the above-mentioned method for preparing an electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste, the addition amounts of the molybdenum source and the sulfur source are controlled so that the molar ratio of molybdenum to sulfur is (0.2-2.0):1; The molybdenum source is one of sodium molybdate and ammonium molybdate; The sulfur source is one of sulfur powder, thiourea, thioacetamide, mercaptan, L-cysteine, and sodium sulfate; The solvent is water or an aqueous solution of ethanol; as an example, the mass concentration of the aqueous solution of ethanol is 10%; As an example, the mass volume ratio of the sulfur source to the solvent is 1.2 g:60 mL.
[0008] In the above-mentioned method for preparing an electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste, the solvent thermal reaction is carried out in a reaction kettle, the reaction temperature is 180°C to 220°C, the reaction time is 18 to 24 h, preferably at 220°C for 22 to 24 h; The method further comprises the step of vacuum drying the product after the solvothermal reaction.
[0009] In the above-mentioned preparation method of the electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste, each 50 × 50 × 0.1 mm 3 The titanium-based ruthenium-iridium electrode is mixed with 0.5 to 2.5 g of the MoS2-based piezoelectric material; preferably, each 50 × 50 × 0.1 mm 3 The titanium-based ruthenium-iridium electrode is mixed with 2.5 g of the MoS2-based piezoelectric material.
[0010] In the above-mentioned preparation method of the electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste, the hydrothermal reaction is carried out in a reaction kettle at a temperature of 180° C. to 220° C. and a reaction time of 12 to 16 h; The method further comprises a step of drying the product after the hydrothermal reaction.
[0011] In a second aspect, the present invention provides a piezoelectric catalytic electrode for deep dehydration of organic solid waste obtained by any of the preparation methods described above.
[0012] In a third aspect, the present invention provides a method for deep dehydration of organic solid waste, comprising the following steps: The electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste is used as an anode plate and a cathode plate respectively, and the organic solid waste to be treated is used as an electrolyte. By applying voltage, deep dehydration of the organic solid waste can be achieved.
[0013] Based on the above technical scheme, the present invention prepares a nano-flower-shaped MoS2 piezoelectric material with strong piezoelectric response ability and defective edge structure by directional regulation and preparation, and compounding it with a commercial titanium-based ruthenium-iridium electrode to prepare a piezoelectric catalytic electrode material. On this basis, through the electrocatalytic system, the Zeta potential of the interface between organic solid waste and solution is effectively adjusted, the extracellular polymer structure on the surface of organic solid waste is destroyed, bound water and interstitial water are released, and the deep dehydration and reduction efficiency of organic solid waste is improved, which has good market application potential.
[0014] In the above-mentioned method for deep dehydration of organic solid waste, the organic solid waste is one or more of kitchen waste, river and lake sediment, and engineering mud; The moisture content of the organic solid waste is 40% to 60%.
[0015] In the above-mentioned method for deep dehydration of organic solid waste, the distance between the anode plate and the cathode plate is 1 to 5 cm.
[0016] In the above-mentioned method for deep dehydration of organic solid waste, the electrolytic treatment adopts the following mode 1) or mode 2): 1) Constant voltage mode, the voltage intensity is 0.50-1.25 V, preferably 0.75-1 V, and the running time is 5-10 minutes, preferably 5 minutes; 2) Pulse voltage mode, with a voltage intensity of ±1 V, a pulse cycle of 10 s, and a running time of 5 to 10 minutes, preferably 8 minutes.
[0017] The basic principle and advantages of the present invention: The piezoelectric catalytic electrode material is compounded with a nano-flower-shaped MoS2 piezoelectric material with a defect structure and a commercial titanium-based ruthenium-iridium electrode. By adjusting the molybdenum-sulfur molar ratio to construct a MoS2 piezoelectric material rich in molybdenum defects and sulfur defects, especially a MoS2 piezoelectric material rich in molybdenum defects, the self-polarization performance of the piezoelectric material driven by the electric field is improved, and a piezoelectric local amplification effect is generated at the defect structure, the piezoelectric electric field and the residual electric field strength are increased, and the generation of active species is promoted. Without adding chemical agents, the Zeta potential of the interface between organic solid waste and solution can be adjusted, the extracellular polymer structure on the surface of organic solid waste can be destroyed, and bound water and interstitial water can be released, thereby improving the deep dehydration and reduction efficiency of organic solid waste. The overall moisture content of organic solid waste is further reduced from 40% to 60% to 30.7% to 46.3%, and the deep dehydration efficiency is as high as 9.3% to 13.7%. This technical solution has the advantages of low cost and energy consumption, no secondary pollution risk, simple equipment and easy implementation. It provides an efficient solution for the deep dehydration of organic solid waste and can be used for the deep dehydration of organic solid waste such as food waste, river and lake sediments, and engineering mud. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings: Figure 1 X-ray diffraction spectra of MoS2, molybdenum-rich defect MoS2, and sulfur-rich defect MoS2 piezoelectric materials prepared in the embodiments of the present invention.
[0019] Figure 2 This is an atomic force micrograph of the MoS2 piezoelectric material prepared in Example 1 of the present invention.
[0020] Figure 3 This is the atomic force-piezoelectric response diagram of the MoS2 piezoelectric material prepared in Example 1 of the present invention.
[0021] Figure 4 This is the hysteresis loop-piezoelectric butterfly curve diagram of the MoS2 piezoelectric material prepared in Example 1 of the present invention.
[0022] Figure 5 This is an atomic force micrograph of the sulfur-rich defect MoS2 piezoelectric material prepared in Example 2 of the present invention.
[0023] Figure 6 This is the atomic force-piezoelectric response diagram of the sulfur-defective MoS2 piezoelectric material prepared in Example 2 of the present invention.
[0024] Figure 7This is an atomic force micrograph of the molybdenum-defective MoS2 piezoelectric material prepared in Example 3 of the present invention.
[0025] Figure 8 This is the atomic force-piezoelectric response diagram of the molybdenum-rich defect MoS2 piezoelectric material prepared in Example 3 of the present invention.
[0026] Fig. 9 This is the hysteresis loop-piezoelectric butterfly curve diagram of the molybdenum-rich defect MoS2 piezoelectric material prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0028] The methods used in the following examples, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0029] The commercial titanium-based ruthenium-iridium electrode in the following embodiments is a sessile ruthenium-iridium-titanium mesh produced by Suzhou Shultai Industrial Technology Co., Ltd., which is cut into 50 mm × 50 mm × 1 mm for standby use.
[0030] The food waste in the following embodiments comes from canteen food waste.
[0031] Example 1: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.5:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220 °C for 24 h. The solid product was vacuum dried to obtain a nanoflower-like MoS2 piezoelectric material (XRD spectrum see Figure 1 , atomic force microscopy images are shown in Figure 2 ). Combined with the atomic force-piezoelectric response diagram of MoS2 piezoelectric material (attached Figure 3 ) The piezoelectric response is concentrated at the edge of MoS2 particles, and the piezoelectric coefficient d 33 The complete butterfly ring and hysteresis loop prove the piezoelectric performance of MoS2 catalytic material (see Appendix Figure 4 ).
[0032] 0.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain the MoS2 piezoelectric catalytic electrode material for later use.
[0033] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 40% to 45%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0034] At the end of the operation, the moisture content of organic solid waste dropped from 40%-45% to 30.5%-35.5%, and the calculated deep dehydration rate of organic solid waste was 9.5%.
[0035] Example 2: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220 °C for 24 h. The solid product was vacuum dried to obtain sulfur-defective nanoflower-like MoS2 piezoelectric material (XRD spectrum see Figure 1 , atomic force microscopy images are shown in Figure 5 ). Atomic force-piezoelectric response diagram of MoS2 piezoelectric material with sulfur defects (attached Figure 6 ) The piezoelectric response is still concentrated at the edges of MoS2 particles.
[0036] 0.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain the sulfur-deficient MoS2 piezoelectric catalytic electrode material for later use.
[0037] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 40% to 45%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0038] At the end of the operation, the moisture content of organic solid waste dropped from 40%-45% to 30.4%-35.4%, and the calculated deep dehydration rate of organic solid waste was 9.6%.
[0039] Example 3: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a polytetrafluoroethylene-lined reactor and reacted at 220 °C for 24 h. The solid product was vacuum dried to obtain a molybdenum-defective nanoflower-like MoS2 piezoelectric material (XRD spectrum see Figure 1 , atomic force microscopy images are shown in Figure 7 ). Atomic force-piezoelectric response diagram of MoS2 piezoelectric material with molybdenum defects (attached Figure 8 ), the piezoelectric response is concentrated on the surface of MoS2 particles, and the piezoelectric coefficient d 33 The piezoelectric performance of the molybdenum-deficient MoS2 catalytic material is 51.58 pm / V, and the good butterfly ring and hysteresis loop prove the piezoelectric performance of the molybdenum-deficient MoS2 catalytic material (attached Fig. 9 ).
[0040] 0.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0041] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 40% to 45%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0042] At the end of the operation, the moisture content of organic solid waste dropped from 40% to 45% to 29.8% to 34.8%, and the calculated deep dehydration rate of organic solid waste was 10.2%.
[0043] It can be seen from Examples 1 to 3 that the molar ratio of the molybdenum source to the sulfur source can be adjusted within the range of (0.2 to 2):1, and the nanoflower-shaped MoS2 piezoelectric materials with different defect structures prepared from molybdenum sources and sulfur sources with different molar ratios all have good piezoelectric properties, and the piezoelectric catalytic electrodes further compounded with titanium-based ruthenium iridium electrodes can achieve deep dehydration of organic solid waste. Among them, when the molar ratio of molybdenum to sulfur is 0.2:1, the prepared piezoelectric material is a molybdenum-defect nanoflower-shaped MoS2 piezoelectric material, which has the best piezoelectric properties and the highest dehydration rate for organic solid waste.
[0044] Example 4: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0045] 0.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0046] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 40% to 45%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0047] At the end of the operation, the moisture content of organic solid waste changed from 40% to 45% to 29.9% to 34.9%, and the calculated deep dehydration rate of organic solid waste was 10.1%.
[0048] Example 5: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 20 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0049] 0.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0050] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 40% to 45%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0051] At the end of the operation, the moisture content of organic solid waste changed from 40%-45% to 30.1%-35.1%, and the calculated deep dehydration rate of organic solid waste was 9.9%.
[0052] Example 6: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 18 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0053] 0.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0054] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 40% to 45%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0055] At the end of the operation, the moisture content of organic solid waste changed from 40%~45%b to 30.2%~35.2%, and the calculated deep dehydration rate of organic solid waste was 9.8%.
[0056] It can be seen from Examples 3 to 6 that the solvent thermal reaction time can be adjusted within 18 to 24 hours, and the piezoelectric catalytic electrode obtained by combining the molybdenum-deficient MoS2 catalytic material prepared within this time with the titanium-based ruthenium-iridium electrode can achieve deep dehydration of organic solid waste.
[0057] Example 7: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0058] 1.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0059] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 40% to 45%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0060] At the end of the operation, the moisture content of organic solid waste changed from 40% to 45% to 28.7% to 33.7%, and the calculated deep dehydration rate of organic solid waste was 11.3%.
[0061] Example 8: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0062] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0063] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 40% to 45%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0064] At the end of the operation, the moisture content of organic solid waste changed from 40%-45% to 28.1%-33.1%, and the calculated deep dehydration rate of organic solid waste was 11.9%.
[0065] It can be seen from Examples 3, 7 and 8 that for the titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ), the dosage of piezoelectric material can be adjusted in the range of 0.5 to 2.5 g. The piezoelectric catalytic electrode materials obtained by compounding different dosages of piezoelectric materials with titanium-based ruthenium-iridium electrodes can achieve deep dehydration of organic solid waste.
[0066] Example 9: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0067] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0068] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 45% to 50%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0069] At the end of the operation, the moisture content of organic solid waste changed from 45% to 50% to 32.7% to 37.7%, and the calculated deep dehydration rate of organic solid waste was 12.3%.
[0070] Example 10: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0071] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0072] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 50% to 55%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0073] At the end of the operation, the moisture content of organic solid waste changed from 50%-55% to 37.5%-42.5%, and the calculated deep dehydration rate of organic solid waste was 12.5%.
[0074] Example 11: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0075] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0076] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the plate spacing was 5 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 55% to 60%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0077] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 42.1%-47.1%, and the calculated deep dehydration rate of organic solid waste was 12.9%.
[0078] It can be seen from Examples 8-11 that the moisture content of organic solid waste (kitchen waste) can be adjusted within the range of 40% to 60%, and the method of the present invention can achieve deep dehydration of organic solid waste within this moisture content range.
[0079] Example 12: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0080] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0081] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the distance between the plates was 3 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 55% to 60%, and the voltage intensity was 0.50 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0082] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.8%-46.8%, and the calculated deep dehydration rate of organic solid waste was 13.2%.
[0083] Example 13: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0084] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0085] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the distance between the plates was 1 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 55% to 60%, and the voltage intensity was 0.50 V under the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0086] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.6%-46.6%, and the calculated deep dehydration rate of organic solid waste was 13.4%.
[0087] It can be seen from Examples 1-13 that the plate spacing in the present invention can be adjusted within the range of 1 to 5 cm, and the method of the present invention can achieve deep dehydration of organic solid waste within this substrate spacing.
[0088] Example 14: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0089] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0090] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the distance between the plates was 1 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 55% to 60%, and the voltage intensity was 0.75 V under the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0091] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.5%-46.5%, and the calculated deep dehydration rate of organic solid waste was 13.5%.
[0092] Example 15: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0093] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0094] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the distance between the plates was 1 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 55% to 60%, and the voltage intensity was 1V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0095] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.5-46.5%, and the calculated deep dehydration rate of organic solid waste was 13.5%.
[0096] Example 16: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0097] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0098] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the distance between the plates was 1 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 55% to 60%, and the voltage intensity was 1.25 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0099] At the end of the operation, the moisture content of organic solid waste changed from 55% to 60% to 41.7% to 46.7%, and the calculated deep dehydration rate of organic solid waste was 13.3%.
[0100] It can be seen from Examples 13-16 that, under the constant voltage mode, the voltage intensity can be adjusted within the range of 0.50 to 1.25 V, and the method of the present invention can achieve deep dehydration of organic solid waste under this voltage intensity.
[0101] Example 17: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0102] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0103] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the distance between the plates was 1 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 55% to 60%, and the voltage intensity was 0.75 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 8 min.
[0104] At the end of the operation, the moisture content of organic solid waste changed from 55% to 60% to 41.7% to 46.7%, and the calculated deep dehydration rate of organic solid waste was 13.3%.
[0105] Example 18: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0106] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0107] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the distance between the plates was 1 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 55% to 60%, and the voltage intensity was 0.75 V in the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 10 min.
[0108] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.6%-46.6%, and the calculated deep dehydration rate of organic solid waste was 13.4%.
[0109] It can be seen from Examples 14, 17 and 18 that, under the constant voltage mode, the operating time can be adjusted within the range of 5 to 10 minutes, and deep dehydration of organic solid waste can be achieved within this operating time.
[0110] Example 19: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0111] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0112] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material is used as anode and cathode, the distance between the plates is 1 cm, the electrolyte is organic solid waste (kitchen waste) with a water content of 55% to 60%, and under the pulse voltage mode of the voltage stabilizer (DH1766-2), the voltage intensity is ±1V, with a pulse cycle of 10 s, and the operating time is within 5 min.
[0113] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.5%-46.5%, and the calculated deep dehydration rate of organic solid waste was 13.5%.
[0114] Example 20: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0115] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0116] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material is used as anode and cathode, the distance between the plates is 1 cm, the electrolyte is organic solid waste (kitchen waste) with a water content of 55% to 60%, and under the pulse voltage mode of the voltage stabilizer (DH1766-2), the voltage intensity is ±1V, with a pulse cycle of 10 s, and the operating time is within 8 min.
[0117] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.3%-46.3%, and the calculated deep dehydration rate of organic solid waste was 13.7%.
[0118] Example 21: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of 10 wt% ethanol aqueous solution. The mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0119] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0120] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material is used as anode and cathode, the distance between the plates is 1 cm, the electrolyte is organic solid waste (kitchen waste) with a water content of 55% to 60%, and under the pulse voltage mode of the voltage stabilizer (DH1766-2), the voltage intensity is ±1V, with a pulse cycle of 10 s, and the operating time is within 10 min.
[0121] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.3%-46.3%, and the calculated deep dehydration rate of organic solid waste was 13.7%.
[0122] It can be seen from Examples 19-21 that, under the pulse voltage mode, the operating time can be adjusted within the range of 5 to 10 minutes, and deep dehydration of organic solid waste can be achieved within this operating time.
[0123] Example 22: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of water, and the mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0124] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0125] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material was used as the anode and cathode, the distance between the plates was 1 cm, the electrolyte was organic solid waste (kitchen waste) with a water content of 55% to 60%, and the voltage intensity was 0.75 V under the constant voltage mode of the voltage-stabilized power supply (DH1766-2) for 5 min.
[0126] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.5%-46.5%, and the calculated deep dehydration rate of organic solid waste was 13.5%.
[0127] Example 23: Preparation of piezoelectric catalytic electrode material and its application in deep dehydration of organic solid waste 1. Preparation of piezoelectric catalytic electrode materials Sodium molybdate and thiourea (1.2 g) with a molar ratio of molybdenum to sulfur of 0.2:1 were fully mixed with 60 mL of water, and the mixed solution was placed in a reactor lined with polytetrafluoroethylene and reacted at 220°C for 22 h. After the solid product was vacuum dried, a molybdenum-defective nanoflower-like MoS2 piezoelectric material was obtained.
[0128] 2.5 g of piezoelectric material was placed on a commercial titanium-based ruthenium-iridium electrode (50 × 50 × 0.1 mm 3 ) was added to 50 mL of deionized water solution and mixed thoroughly, then transferred to a reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180 °C for 12 h. After the reaction, a commercial titanium-based ruthenium-iridium electrode was taken out and dried in an oven at 80 °C for 2 h to obtain a molybdenum-defective MoS2 piezoelectric catalytic electrode material for later use.
[0129] 2. Deep dehydration of organic solid waste The above-mentioned piezoelectric catalytic electrode material is used as anode and cathode, the distance between the plates is 1 cm, the electrolyte is organic solid waste (kitchen waste) with a water content of 55% to 60%, and under the pulse voltage mode of the voltage stabilizer (DH1766-2), the voltage intensity is ±1V, with a pulse cycle of 10 s, and the operating time is within 8 min.
[0130] At the end of the operation, the moisture content of organic solid waste changed from 55%-60% to 41.3%-46.3%, and the calculated deep dehydration rate of organic solid waste was 13.7%.
[0131] It can be seen from Examples 14, 20, 22 and 23 that the catalytic electrode materials prepared from different precursors can achieve deep dehydration of organic solid waste under different voltage modes.
[0132] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, can implement the present invention in a wider range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.
Claims
1. A method for preparing an electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste, characterized in that: The steps include: S1, mixing a molybdenum source, a sulfur source and a solvent for a solvothermal reaction to obtain a MoS2-based piezoelectric material; The MoS2-based piezoelectric material includes any one of a MoS2 piezoelectric material, a sulfur-defective MoS2 piezoelectric material, and a molybdenum-defective MoS2 piezoelectric material; S2. Mix the MoS2-based piezoelectric material, titanium-based ruthenium-iridium electrode and water to carry out a hydrothermal reaction to obtain the electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste.
2. The method for preparing an electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste according to claim 1, characterized in that: The addition amounts of the molybdenum source and the sulfur source are controlled so that the molar ratio of molybdenum to sulfur is (0.2-2.0):1, preferably 0.2:1; The molybdenum source is one of sodium molybdate and ammonium molybdate; The sulfur source is one of sulfur powder, thiourea, thioacetamide, mercaptan, L-cysteine, and sodium sulfate; The solvent is water or an aqueous solution of ethanol.
3. The method for preparing an electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste according to any one of claims 1-2, characterized in that: The solvent thermal reaction is carried out in a reaction vessel at a reaction temperature of 180°C to 220°C for 18 to 24 hours, preferably at 220°C for 22 to 24 hours; The method further comprises the step of vacuum drying the product after the solvothermal reaction.
4. The method for preparing an electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste according to any one of claims 1 to 3, characterized in that: Each 50 × 50 × 0.1 mm 3 The titanium-based ruthenium-iridium electrode is mixed with 0.5 to 2.5 g of the MoS2-based piezoelectric material; preferably, each 50 × 50 × 0.1 mm 3 The titanium-based ruthenium-iridium electrode is mixed with 2.5 g of the MoS2-based piezoelectric material.
5. The method for preparing an electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste according to any one of claims 1 to 4, characterized in that: The hydrothermal reaction is carried out in a reactor at a temperature of 180°C to 220°C and a reaction time of 12 to 16 hours; The method further comprises a step of drying the product after the hydrothermal reaction.
6. An electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste obtained by the preparation method according to any one of claims 1 to 5.
7. A method for deep dehydration of organic solid waste, characterized in that: The steps include: By using the electrically driven piezoelectric catalytic electrode for deep dehydration of organic solid waste as claimed in claim 6 as the anode plate and the cathode plate, respectively, and the organic solid waste to be treated as the electrolyte, and applying voltage, deep dehydration of the organic solid waste can be achieved.
8. The method for deep dehydration of organic solid waste according to claim 7, characterized in that: The organic solid waste is one or more of kitchen waste, river and lake sediment, and engineering mud; The moisture content of the organic solid waste is 40% to 60%.
9. The method for deep dehydration of organic solid waste according to any one of claims 7-8, characterized in that: The distance between the anode plate and the cathode plate is 1 to 5 cm, preferably 1 cm.
10. The method for deep dehydration of organic solid waste according to any one of claims 7 to 9, characterized in that: The electrolytic treatment adopts the following mode 1) or mode 2): 1) Constant voltage mode, the voltage intensity is 0.50-1.25 V, preferably 0.75-1 V, and the running time is 5-10 minutes, preferably 5 minutes; 2) Pulse voltage mode, with a voltage intensity of ±1 V, a pulse cycle of 10 s, and a running time of 5 to 10 min, preferably 8 min.
Citation Information
Patent Citations
Composite piezoelectric catalytic material and preparation method and sludge dewatering application thereof
CN111068659A
Graphite felt loaded two-dimensional layered nanosheet electro-Fenton cathode material as well as preparation method and application thereof
CN112811536A
Preparation method of ultrathin molybdenum disulfide crystal nano composite material taking titanium mesh as substrate as well as product and application
CN113755827A
Preparation method of (002) interplanar spacing widened and multi-defect MoS2 adsorbent as well as product and application thereof
CN115463638A
Composite material for sludge dewatering, preparation method of composite material and sludge dewatering conditioner
CN117865435A
